2015
DOI: 10.1021/acs.nanolett.5b03283
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Dynamic Synapse with Modulatable Plasticity

Abstract: The synaptic activities in the nervous system is the basis of memory and learning behaviors, and the concept of biological synapse has also spurred the development of neuromorphic engineering. In recent years, the hardware implementation of the biological synapse has been achieved based on CMOS circuits, resistive switching memory, and field effect transistors with ionic dielectrics. However, the artificial synapse with regulatable plasticity has never been realized of the device level. Here, an artificial dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
216
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(221 citation statements)
references
References 31 publications
4
216
1
Order By: Relevance
“…And a memory cell based on a vertically stacked monolayer MoS 2 /h‐BN/monolayer graphene heterostructure was demonstrated by Vu et al Furthermore, Zhou and co‐workers observed nonvolatile charge‐trap memory in MoS 2 and WSe 2 layers with 3D charge‐trap gate stack . At the same time, artificial synapses based on multilayer 2D materials were also realized in twisted bilayer graphene and multilayer MoS 2 . However, to the best of our knowledge, an ultrathin memristive synapse based on monolayer 2D materials has yet to be realized.…”
Section: Introductionmentioning
confidence: 96%
“…And a memory cell based on a vertically stacked monolayer MoS 2 /h‐BN/monolayer graphene heterostructure was demonstrated by Vu et al Furthermore, Zhou and co‐workers observed nonvolatile charge‐trap memory in MoS 2 and WSe 2 layers with 3D charge‐trap gate stack . At the same time, artificial synapses based on multilayer 2D materials were also realized in twisted bilayer graphene and multilayer MoS 2 . However, to the best of our knowledge, an ultrathin memristive synapse based on monolayer 2D materials has yet to be realized.…”
Section: Introductionmentioning
confidence: 96%
“…Similar behavior of restricting lateral growth of filaments has been also reported in Au/(PEA) 2 PbBr 4 /Gr vertical structure. [64] Copyright 2015, American Chemical Society Publishing. At this current level, basic behaviors of synapse plasticity including EPSC, IPSC, STP, and LTP have been demonstrated.…”
Section: Vertical Devicesmentioning
confidence: 99%
“…Memristive devices relying on charge-trapping effect [64][65][66][67][68][69][70] at the interface are not suitable for development of robust devices, as it is difficult to control the trapping/detrapping process in a reliable way. The unique physical properties that 2D layered materials and vdW heterostructure possess have not been fully exploited for designing neuromorphic devices with new working principles.…”
Section: Introductionmentioning
confidence: 99%
“…The number of reports on 2D materials‐based synaptic devices has accordingly increased rapidly. The most representative 2D materials in the aforementioned are graphene, transition metal dichalcogenides (TMDs) (e.g., MoS 2 and WSe 2 ), black phosphorus (BP), hexagonal boron nitride (h‐BN), and various vdW heterostructures with these 2D materials …”
Section: Introductionmentioning
confidence: 99%